Binnenschiffe auf simulierter Fahrt. Untersuchungen zum Binnenschiffsverkehr am Maritimen Simulationszentrum in Warnemünde. - Baldauf, Michael; Benedict, Knud; Herberg, Sven; Kirchoff, Matthias (Deutscher Verkehrs-Verl., 2004)
Das Maritime Simulationszentrum Warnemünde (MSCW) wurde 1998 an die Hochschule Wismar, University of Technology, Business and Design, Fachbereich Seefahrt, übergeben. Es besteht aus den drei Einzelsystemen Schiffsführungssimulator (Ship Handling Simulator - SHS), Schiffsmaschinensimulator (SES) und Vessel-Traffic-Service-Simulator (VTSS). Durch die Möglichkeit zur Kopplung aller Simulatoren ist das Zentrum einzigartig in der Welt für Trainingsaufgaben und zur Untersuchung von Forschungs- und Entwicklungsaufgaben vornehmlich im Bereich der Hochseeschifffahrt geeignet. Inzwischen wurde das Simulationsspektrum des Zentrums noch erweitert. So wurden unter anderem Untersuchungen zum Binnenschiffsverkehr auf der neuen Hohensaaten-Friedrichstaler-Wasserstraße und dem Main (Vorhafen Eddersheim) durchgeführt. difu

The use of simulators plays a very important role to investigate the layout of inland waterways in the design process to adapt these transport lanes to new demands. The Shiphandling Simulator is one of the core elements of the Wismar Universities simulation centre which was originally dedicated for training and research with seagoing vessels. Now it has been also used to develop various simulation models of inland vessels and waterways to investigate specific scenarios on how to guarantee a risk free and economic layout of the waterway and safe operation of the ships. The assessment of the trail data were made by a specific computer program to screen through the simulation results. From recorded data the ships dimension, contour and track radius were set into relation to the fairway dimensions. These parameters achieved by using a sophisticated simulator environment were used as a basis for decisions to be made for the final fairway design. difu
Keywords: Verkehr; Wasserverkehr; Binnenschiffsverkehr; Simulation; Simulationsmodell; Forschungszentrum; Binnenwasserstraße